Dominant role of benthic photosynthesis for the metabolism of carbonate sands in a subtropical inner shelf - Alireza Merikhi; Peter Berg; Markus Huettel (Limnology and Oceanography, 2025)
Carbonate coral sands are an integral part of the carbon and nutrient cycles in subtropical and tropical coastal environments. Recent studies indicate that nearshore carbonate sands may be hotspots for organic matter production and respiration, but the processes and their controls are poorly understood due to a lack of noninvasive in situ measurements. We deployed a new triple‐sensor aquatic eddy covariance instrument to quantify seasonal O 2 ‐fluxes over a coral sand platform at ~ 10 m water depth in the Florida Keys. The noninvasive measurements revealed the strong influences of light and bottom currents on magnitude and dynamics of the benthic metabolism. Light penetration through the clear water column facilitated substantial microphytobenthos production, making the seafloor a source of oxygen during daylight hours. Daytime benthic O 2 release to the water column ranged between 0.6 mmol O 2 m −2 h −1 (winter) and 4.8 mmol O 2 m −2 h −1 (summer), while nighttime sediment O 2 respiration varied between −1.2 mmol O 2 m −2 h −1 (winter) and −3.3 mmol O 2 m −2 h −1 (summer). Bottom currents modulated the fluxes, emphasizing the role of advective pore water exchange for biogeochemical reactions in the highly permeable sediment. Similar magnitudes and dynamics of daytime sediment O 2 release and nighttime O 2 uptake revealed a tight coupling between production and degradation of highly labile photosynthetic products. We use the results to explain why O 2 respiration rates in permeable carbonate sands of oligotrophic subtropical/tropical environments can reach similar magnitudes as those reported from permeable silicate sand beds of nutrient‐rich temperate inner shelves.

Effects of Petroleum By-Products and Dispersants on Ecosystems - Kenneth Halanych; Cameron Ainsworth; Erik Cordes; Richard Dodge; Markus Huettel; Irving Mendelssohn; Steven Murawski; Claire Paris-Limouzy; Patrick Schwing; Richard Shaw; Tracey Sutton (Oceanography, 2021)
Gulf of Mexico (GOM) ecosystems are interconnected by numerous physical and biological processes. After the Deepwater Horizon (DWH) disaster, these ecological processes facilitated dispersal of oil-spill toxicants or were damaged and broken. A considerable portion of post-DWH research focused on higher levels of biological organization (i.e., populations, communities, and ecosystems) spanning at least four environments (onshore, coastal, open ocean, and deep benthos). Damage wrought by the oil spill and mitigation efforts varied considerably across ecosystems. Whereas all systems show prolonged impacts because of cascading effects that impacted functional connections within and between communities, deep-sea and mesopelagic environments were particularly hard hit and have shown less resilience than shallow environments. In some environments, such as marshes or the deep-sea benthos, products from the spill are still biologically accessible. Some shallow ecosystems show signs of recovery, and populations of some species show resilience; however, a return to a “pre-spill” state is questionable. Importantly, habitats in which large amounts of energy flow through the ecosystem (marshes, coastal regions) recovered more quickly than low energy habitats (deep-sea benthos). Functional interactions between Gulf of Mexico systems are more complex and widespread than generally recognized. Moreover, ecosystems in the Gulf are subject to multiple stressors that can combine to impart greater, and less predictable, impacts. To help mitigate the effects of future insults, we identified four salient areas of research that should be addressed for each of the major environments within the GOM: establishing monitoring systems; quantifying coupling between GOM ecosystems; developing criteria for assessing the “vulnerability” and “resilience” of species, communities, and ecosystems; and developing holistic predictive modeling.

Genome repository of oil systems: An interactive and searchable database that expands the catalogued diversity of crude oil‐associated microbes - Smruthi Karthikeyan; Luis M. Rodriguez‐R; Patrick Heritier‐Robbins; Janet K. Hatt; Markus Huettel; Joel E. Kostka; Konstantinos T. Konstantinidis (Environmental Microbiology, 2020)
Summary Microbial communities ultimately control the fate of petroleum hydrocarbons (PHCs) that enter the natural environment, but the interactions of microbes with PHCs and the environment are highly complex and poorly understood. Genome‐resolved metagenomics can help unravel these complex interactions. However, the lack of a comprehensive database that integrates existing genomic/metagenomic data from oil environments with physicochemical parameters known to regulate the fate of PHCs currently limits data analysis and interpretations. Here, we curated a comprehensive, searchable database that documents microbial populations in natural oil ecosystems and oil spills, along with available underlying physicochemical data, geocoded via geographic information system to reveal their geographic distribution patterns. Analysis of the ~2000 metagenome‐assembled genomes (MAGs) available in the database revealed strong ecological niche specialization within habitats. Over 95% of the recovered MAGs represented novel taxa underscoring the limited representation of cultured organisms from oil‐contaminated and oil reservoir ecosystems. The majority of MAGs linked to oil‐contaminated ecosystems were detectable in non‐oiled samples from the Gulf of Mexico but not in comparable samples from elsewhere, indicating that the Gulf is primed for oil biodegradation. The repository should facilitate future work toward a predictive understanding of the microbial taxa and their activities that control the fate of oil spills.

Biogeochemistry of a River-Dominated Estuary Influenced by Drought and Storms - Natalie Geyer; Markus Huettel; Michael Wetz (Estuaries and Coasts, 2018)

Phytoplankton Spatial Variability in the River-Dominated Estuary, Apalachicola Bay, Florida - Natalie L. Geyer; Markus Huettel; Michael S. Wetz (Estuaries and Coasts, 2018)

Seafood and Beach Safety in the Aftermath of the Deepwater Horizon Oil Spill - Robert Dickey; Markus Huettel (Oceanography, 2016)

Temperature response of denitrification and anaerobic ammonium oxidation rates and microbial community structure in A rctic fjord sediments - Andy Canion; Will A. Overholt; Joel E. Kostka; Markus Huettel; Gaute Lavik; Marcel M. M. Kuypers (Environmental Microbiology, 2014)
Summary The temperature dependency of denitrification and anaerobic ammonium oxidation (anammox) rates from A rctic fjord sediments was investigated in a temperature gradient block incubator for temperatures ranging from −1 to 40°C. Community structure in intact sediments and slurry incubations was determined using Illumina SSU rRNA gene sequencing. The optimal temperature ( T opt ) for denitrification was 25–27°C, whereas anammox rates were optimal at 12–17°C. Both denitrification and anammox exhibited temperature responses consistent with a psychrophilic community, but anammox bacteria may be more specialized for psychrophilic activity. Long‐term (1–2 months) warming experiments indicated that temperature increases of 5–10°C above in situ had little effect on the microbial community structure or the temperature response of denitrification and anammox. Increases of 25°C shifted denitrification temperature responses to mesophilic with concurrent community shifts, and anammox activity was eliminated above 25°C. Additions of low molecular weight organic substrates (acetate and lactate) caused increases in denitrification rates, corroborating the hypothesis that the supply of organic substrates is a more dominant control of respiration rates than low temperature. These results suggest that climate‐related changes in sinking particulate flux will likely alter rates of N removal more rapidly than warming.

Ebullition‐enhanced solute transport in coarse‐grained sediments - Chiu H. Cheng; Markus Huettel; Richard A. Wildman (Limnology and Oceanography, 2014)
Pore‐water exchange caused by ebullition of small oxygen bubbles produced by microalgae in the surface layer of sand sediment at St. Joseph Bay (SJB), Gulf of Mexico, was contrasted with ebullition of larger methane bubbles generated by archaea in deeper layers of sub‐littoral sands at Hel Peninsula (HEL), Baltic Sea. At SJB, ebullition of O 2 ‐enriched bubbles in August 2011 averaged 225 ± 132 mL m −2 d −1 , and at a mean bubble diameter of 1.0 ± 0.3 mm, up to 516,000 bubbles m2 −2 d −1 were released from the upper 10 mm of sediment. Ebullition of CH 4 ‐enriched bubbles at HEL reached 907 ± 278 mL m2 −2 d2 −1 in August 2003, with bubbles of 10–20 mm diameter ascending from > 100 mm sediment depth at a rate of up to 210 bubbles m −2 d −1 . In situ chamber experiments showed that ebullition of 12 mm diameter bubbles from 80 mm sediment depth at a rate of ~ 5 mL min −1 (254 L m −2 d −1 ) enhanced interfacial fluid flux ~ three‐fold compared to chambers with no ebullition. In contrast, release of 2 mm diameter bubbles from 3 mm sediment depth at a lower rate of ~ 1 mL min −1 increased interfacial flux about 21‐fold in laboratory tests, revealing that frequent ebullition of small bubbles released near the sediment surface enhances sediment‐water fluid flux more effectively than ebullition of larger bubbles ascending from deeper sediment depths at low frequency. Particle image velocimetry showed that bubble ebullition effectively entrained pore fluid into the turbulent boundary layer, thereby enhancing benthic pelagic coupling.

Eddy correlation measurements of oxygen fluxes in permeable sediments exposed to varying current flow and light - Peter Berg; Matthew H. Long; Markus Huettel; Jennie E. Rheuban; Karen J. McGlathery; Robert W. Howarth; Kenneth H. Foreman; Anne E. Giblin; Roxanne Marino (Limnology and Oceanography, 2013)
Based on noninvasive eddy correlation measurements at a marine and a freshwater site, this study documents the control that current flow and light have on sediment‐water oxygen fluxes in permeable sediments. The marine sediment was exposed to tidal‐driven current and light, and the oxygen flux varied from night to day between −29 and 78 mmol m −2 d −1 . A fitting model, assuming a linear increase in oxygen respiration with current flow, and a photosynthesis‐irradiance curve for light‐controlled production reproduced measured fluxes well ( R 2 = 0.992) and revealed a 4‐fold increase in oxygen uptake when current velocity increased from ∼ 0 to 20 cm s −1 . Application of the model to a week‐long measured record of current velocity and light showed that net ecosystem metabolism varied substantially among days, between −27 and 31 mmol m −2 d −1 , due to variations in light and current flow. This variation is likely typical of many shallow‐water systems and highlights the need for long‐term flux integrations to determine system metabolism accurately. At the freshwater river site, the sediment‐water oxygen flux ranged from −360 to 137 mmol m −2 d −1 . A direct comparison during nighttime with concurrent benthic chamber incubations revealed a 4.1 times larger eddy flux than that obtained with chambers. The current velocity during this comparison was 31 cm s −1 , and the large discrepancy was likely caused by poor imitation by the chambers of the natural pore‐water flushing at this high current velocity. These results emphasize the need for more noninvasive oxygen flux measurements in permeable sediments to accurately assess their role in local and global carbon budgets.

Discharge of dissolved black carbon from a fire‐affected intertidal system - Thorsten Dittmar; Jiyoung Paeng; Thomas M. Gihring; I G. N. A. Suryaputra; Markus Huettel (Limnology and Oceanography, 2012)
We report substantial tidal fluxes of dissolved black carbon (DBC) in a fire‐affected marsh in the northern Gulf of Mexico. DBC was molecularly determined as benzenepolycarboxylic acids in a tidal creek, adjacent rivers, and the coastal ocean. Supported by stable carbon isotope and in situ fluorescence measurements, three sources of dissolved organic carbon (DOC) were identified that mixed conservatively in the coastal system: groundwater from salt marshes, river water, and seawater. Groundwater was the main source of DBC to the creek. The highest DBC concentrations of up to 41 µmol C L −1 (7.2% of DOC) were found in the creek at low tide, compared with −1 in all other samples. Over the studied tidal cycle, we determined a runoff (load per drainage area) of 3700 moles DBC (44 kg C) km −2 of salt marsh. This is high compared with the Apalachicola River, where the annual DBC runoff is on the order of 10 4 mol (120 kg C) km −2 yr −1 . In the marsh, it would require ∼ 20 tidal cycles similar to the one that we studied to remove all black carbon produced during one fire event. Because a spring tide was studied, our estimate is as an upper limit. DBC is ubiquitous in the global ocean, and dissolution and subsequent lateral transport appear to be important removal mechanisms for soil black carbon. Our study, which provides a snapshot in time and space, demonstrates that tidal fluxes may be primary carriers of DBC, and therefore tidal pumping and groundwater discharge cannot be ignored in assessing the continental runoff of DBC.

Decomposition of plankton‐derived dissolved organic matter in permeable coastal sediments - Lindsay Chipman; David Podgorski; Stefan Green; Joel Kostka; William Cooper; Markus Huettel (Limnology and Oceanography, 2010)
We tested the hypothesis that dissolved organic carbon (DOC) is degraded when filtered through permeable shelf sediments. In a laboratory flume experiment the concave shape of DOC profiles observed in the upper 10 cm of Gulf of Mexico sublittoral sands was reproduced by the combination of DOC filtration and production in the sediment surface layer and mineralization and adsorption in the subsurface layer. Six percent to 14% of 13 C‐labeled, highly degradable DOC was mineralized during filtration through 5.8‐cm‐long sand‐filled column reactors, up to nine times more than in dark, water‐filled column reactors. Filtration through 50‐cm‐long sand columns removed all highly degradable DOC pumped through the sediment, translating to fluxes of up to 379 mmol DOC m −2 d −1 , corresponding to DOC removal from an approximately 1‐m‐deep water layer each day. Bacterial incorporation of 13 C identified a diverse group of sedimentary aerobic and anaerobic microbes processing DO 13 C filtered through sand columns, dominated by Gammaproteobacteria , Deltaproteobacteria , Firmicutes , Bacteroidetes , and Planctomycetes . Excitation‐emission matrix spectroscopy analysis of chromophoric dissolved organic matter contained in diatom‐derived DOC indicated that microbes preferentially removed components around the fluorescence peak of tryptophan or protein‐like substances, which may have the highest nutrient value. Mass spectra analysis revealed that filtration through sand also removes a broad spectrum of substances from less degradable humic and fulvic acid‐like DOC and produces new DOC components. The flushed sand layer between the water column and deeper anoxic sediment layers acts as an effective DOC filter, with subsurface horizontal pore‐water flows promoting decomposition of DOC.

Denitrification in shallow, sublittoral Gulf of Mexico permeable sediments - Thomas M. Gihring; Andy Canion; Ashley Riggs; Markus Huettel; Joel E. Kostk (Limnology and Oceanography, 2010)
We examined nitrogen cycling over a 1‐yr period in shallow, sandy sediments at two contrasting sites near a barrier island in the northeastern Gulf of Mexico, and we provide here the direct determination of dinitrogen gas (N 2 ) production at ambient nitrate concentrations in permeable marine sediments. Nitrogen‐stable isotope tracer techniques were used to quantify N 2 ‐production rates and pathways in sediment cores and slurries. To simulate pore‐water advection, the dominant transport process in the upper layer of the permeable sand beds, intact sediment cores were perfused with aerated seawater. This perfusion increased denitrification rates up to 2‐fold in Apalachicola Bay sands and up to 17‐fold in Gulf of Mexico sublittoral sands, respectively, relative to static cores. Seasonal N 2 ‐production rates were highest in spring and fall. Denitrified nitrate originated almost entirely from benthic nitrification at the exposed Gulf site, whereas water‐column nitrate dominated sedimentary denitrification at the sheltered Bay site. Sediment incubations in stirred chambers were used to determine net fluxes of oxygen (O 2 ), N 2 , nitrate, and ammonium across the sediment‐water interface during varied degrees of continuous pore‐water exchange. Rates of N 2 efflux correlated with rates of pore‐water flow increasing from 0.12 mmol N m ‐2 d ‐1 under diffusion‐limited transport conditions up to 0.87 mmol N m ‐2 d ‐1 with pore‐water advection. Mineralized nitrogen was completely converted to N 2 gas in Gulf of Mexico sediments. Our results demonstrate that advective pore‐water circulation will accelerate benthic N 2 production by coupled nitrification‐ denitrification and that substantial nitrogen loss occurs from coastal permeable sediments.

Sulfide assimilation by ectosymbionts of the sessile ciliate, Zoothamnium niveum - Hans Røy; Kay Vopel; Markus Huettel; Bo Barker Jørgensen (Marine Biology, 2009)

Monitoring the Seafloor Using the Noninvasive Eddy Correlation Technique: Integrated Benthic Exchange Dynamics - Peter Berg; Markus Huettel (Oceanography, 2008)

Benthic solute exchange and carbon mineralization in two shallow subtidal sandy sediments: Effect of advective pore‐water exchange - Perran L. M. Cook; Frank Wenzhöfer; Ronnie N. Glud; Felix Janssen; Markus Huettel (Limnology and Oceanography, 2007)
We conducted four field campaigns to evaluate benthic O 2 consumption and the effect of advective pore‐water flow in nearshore permeable sediments in the North Sea and Baltic Sea. Advective pore‐water transport had a marked effect on the benthic exchange of O 2 and TCO 2 in benthic chamber incubations, with the rates of exchange increasing by a factor of up to 2.5 when imposing flushing rates of 100‐300 L m −2 d −1 , compared to settings with diffusive exchange only. Estimates of in situ exchange rates using oxygen penetration and volumetric O 2 consumption and TCO 2 production rates were within the range measured in the chambers. The contribution of advection to solute exchange was highly variable and dependent on sediment topography. Advective processes also had a pronounced influence on the in situ distribution of O 2 within the sediment, with characteristic two‐dimensional patterns of O 2 distribution across ripples, and also deep subsurface O 2 pools, being observed. Mineralization pathways were predominantly aerobic when benthic mineralization rates were low and advective pore‐water flow high as a result of well‐developed sediment topography. By contrast, mineralization proceeded predominantly through sulfate reduction when benthic mineralization rates were high and advective pore‐water flow low as a result of poorly developed topography. Previous studies of benthic mineralization in shallow sandy sediments have generally ignored these dynamics and, hence, have overlooked crucial aspects of permeable sediment function in coastal ecosystems.

Near-bottom performance of the Acoustic Doppler Velocimeter (ADV) – a comparative study - Elimar Precht; Felix Janssen; Markus Huettel (Aquatic Ecology, 2006)

Spatial and temporal patterns of mineralization rates and oxygen distribution in a permeable intertidal sand flat (Sylt, Germany) - Ursula Werner; Markus Billerbeck; Lubos Polerecky; Ulrich Franke; Markus Huettel; Justus E. E. van Beusekom; Dirk de Beer (Limnology and Oceanography, 2006)
Oxygen distribution and benthic mineralization rates were investigated in a permeable intertidal sand flat (permeability: 3.9 x 10 ‐11 m 2 ) in a transect from the low toward the high waterline. At all stations, oxygen penetrated several millimeters to centimeters into the sediments during inundation because of pore‐water advection. The wave‐ and current‐driven deep oxygen penetration caused high oxygen consumption rates (OCRs) and high aerobic mineralization rates at all stations. Because oxygen penetration was enhanced during inundation, 71‐90% of the daily oxygen consumption took place in that period. OCRs and sulfate reduction rates (SRRs) changed with inundation time of the stations, emphasizing the importance of pore‐water advection for benthic mineralization: OCRs were elevated at the lower flat in summer (lower flat 131‐187; middle and upper flat 64‐108 mmol C m ‐2 d ‐1 ). SRRs increased sharply from the high to the low waterline during all seasons (e.g., in summer: lower flat 18‐40; middle flat 8.8‐9.4, upper flat 0.5‐4 mmol C m ‐2 d ‐1 ). A one‐dimensional model of the advective organic matter supply to the sediment could only explain a fraction of the organic carbon required for benthic mineralization. This suggests that either transport of particles via the seawater is more efficient than the one‐dimensional concept can explain or that additional carbon was supplied through other sources (e.g., benthic photosynthesis). Mineralization rates were higher in summer than in winter. Only in summer did sulfate reduction contribute ≫20% to total mineralization.

Oxygen dynamics in permeable sediments with wave‐driven pore water exchange - Elimar Precht; Ulrich Franke; Lubos Polerecky; Markus Huettel (Limnology and Oceanography, 2004)
The effects of advective pore water exchange driven by shallow water waves on the oxygen distribution in a permeable (k = 3.3 x 10 −12 to 4.9 x 10 −11 m 2 ) natural sediment were studied with a planar oxygen optode in a wave tank. Our experiments demonstrate that pore water flow driven by the interaction of sediment topography and oscillating boundary flow changes the spatial and temporal oxygen distribution in the upper sediment layer. Oxygenated water intruding in the ripple troughs and deep anoxic pore water drawn to the surface under the ripple crests create an undulating oxic‐anoxic boundary within the upper sediment layer, mirroring the topographical features of the sediment bed. Anoxic upwelling zones under ripple crests can separate the oxic sediment areas of neighboring ripple troughs with steep horizontal oxygen concentration gradients. The optode showed that migrating wave ripples are trailed by their pore water flow field, alternately exposing sediment volumes to oxic and anoxic pore water, which can be a mechanism for remobilizing particulate oxidized metal precipitates and for promoting coupled nitrification‐denitrification. More rapid ripple migration (experimental threshold ~20 cm h −1 ) produces a continuous oxic surface layer that inhibits the release of reduced substances from the bed, which under slowly moving ripples is possible through the anoxic vertical upwelling zones. Swift, dramatic changes in oxygen concentration in the upper layers of permeable seabeds because of surface gravity waves require that sediment‐dwelling organisms are tolerant to anoxia or highly mobile and enhance organic matter mineralization.

Transmission of oxygen concentration fluctuations through the diffusive boundary layer overlying aquatic sediments - Hans Røy; Markus Huettel; Bo Barker Jørgensen (Limnology and Oceanography, 2004)
Even though the O 2 concentration in the diffusive boundary layer overlying natural aquatic sediments usually varies over time, microprofiles with little or no error bars are abundant in the literature. These temporal concentration fluctuations are not accounted for in the conceptual models used to describe the diffusive boundary layer, and their effects on phenomena investigated through microprofile measurements are unclear. This paper focuses on concentration fluctuations in the diffusive boundary layer above a marine sediment. One microsensor was inserted into a laboratory flume from below and positioned with the sensing tip precisely at the sediment surface. A second microelectrode was deployed from above through the flowing water column and positioned within the diffusive boundary layer directly above the tip of the lower sensor. Time series of the fluctuating O 2 concentration at the two points were measured simultaneously with the two sensors and demonstrated a tight coupling of concentration fluctuations across the diffusive boundary layer. A dynamic model accounting only for molecular diffusion plus zero‐order O 2 consumption within the sediment explained the observed coupling through the diffusive boundary layer and enabled calculation of instantaneous O 2 profiles from the top of the true diffusive boundary layer to the depth of O 2 penetration. Model results confirmed that concentration fluctuations were linked from the top of the true diffusive boundary layer down to about 0.5 mm sediment depth. The transient profiles moved back and forth, without losing the general shape derived from the averaged steady state O 2 distribution. Apart from this description of the temporal structure of the diffusive boundary layer, the model shows that concentration fluctuations in the layer do not necessarily indicate turbulence within the true diffusive boundary layer. This dynamic description is used to discuss experimental procedures when measuring microprofiles.

Advective pore‐water exchange driven by surface gravity waves and its ecological implications - Elimar Precht; Markus Huettel (Limnology and Oceanography, 2003)
The effects of surface gravity waves on pore‐water release from permeable sediment (k = 1.3–1.8 × 10 −11 m 2 ) in shallow water were studied in a wave tank. Our tracer experiments demonstrated that shallow‐water waves can increase fluid exchange between sandy sediment and overlying water 50‐fold, relative to the exchange by molecular diffusion. The main driving force for this increased exchange are the pressure gradients generated by the interaction of oscillating boundary flows and sediment wave ripples. These gradients produce a pore‐water flow field, with a regular pattern of intrusion and release zones, that migrates with ripple propagation. The ensuing topography‐related filtering rates in the wave tank ranged from 60 to 590 L m −2 d −1 and exceeded the solute exchange rates caused by hydrostatic wave pumping (38 L m −2 d −1 ) and initial molecular diffusion (corresponding to 10–12 L m −2 d −1 ). Wave‐induced filtration is ecologically relevant because permeable sandy sediments are very abundant on the continental margins and can be converted into effective filter systems, which suggests that these sediments are sites for rapid mineralization and recycling. We propose that the wave influenced continental shelf may be subdivided into two zones: a shallow zone (water depth

Hydrodynamical impact on biogeochemical processes in aquatic sediments - Markus Huettel; Hans Røy; Elimar Precht; Sandra Ehrenhauss (Hydrobiologia, 2003)

Advective particle transport into permeable sediments—evidence from experiments in an intertidal sandflat - Markus Huettel; Antje Rusch (Limnology and Oceanography, 2000)
Advective transport of artificial and natural particles into permeable sediments was demonstrated in situ by field experiments in an intertidal Wadden Sea sandflat. Using dyed sediment, advective interfacial solute exchange was shown to reach down at least 1.5 cm below surface. Particle depth distributions depended on sediment permeability and particle size. Sandy sediments were found to efficiently trap particulate material. At the beginning of the local phytoplankton spring bloom, an average m 2 of coarse‐grained sediment received 850‐mg organic carbon per day by filtration of 14 liters of overlying water per hour. We discuss the relative importance of different transport mechanisms, and data from parallel studies on natural sediments at the same site are interpreted in close correlation to the results of the in situ experiment.

Transport and degradation of phytoplankton in permeable sediment - Markus Huettel; Antje Rusch (Limnology and Oceanography, 2000)
In flume and field experiments we demonstrate that interfacial water flows, generated when bottom currents interact with sea bed topography, provide a fast and efficient pathway for the transport of suspended phytoplankton into subsurface layers of permeable sandy sediments. The advective transport, associated with small mounds and ripples as commonly found on shelf sediments, increased penetration depth of unicellular algae ( Dunaliella spec.) into sandy sediment (permeability k = 4 × 10 −11 m 2 ) up to a factor of 7 and flux up to a factor of 9 relative to a smooth control sediment. The pore water flow field produced a distinct distribution pattern of particulate organic matter in the sediment with subsurface concentration maxima and zones depleted of algae. Flux chamber simulations of advective transport of algae into sands of different grain sizes revealed increasing fluxes, algal penetration depths, and degradation rates with increasing permeability of the sediment. Two experiments conducted in intertidal sand flats confirmed the importance of the advective interfacial transport of phytoplankton for natural settings, showing permeability‐dependent penetration of planktonic algae into embedded sand cores of different grain sizes. The significance of our results is discussed with respect to particulate organic matter flux and mineralization in shelf sands, and we suggest the concept of a decomposition layer.